DFT based analysis of pressure driven mechanical, opto-electronic, and thermoelectric properties in lead-free InGeX3 (X = Cl, Br) perovskites for solar energy applications - Md. Ratul Hasan; Imtiaz Ahamed Apon; Md. Mafidul Islam; Asab Uzzaman Azad; Md. Aminuzzman; Md. Salman Haque (AIP Advances, 2024)
Lead halide perovskites have distinct physiochemical properties and demonstrate remarkable power conversion efficiency. We used density functional theory to investigate the electrical, optical, structural, and elastic features of non-toxic InGeCl3 and InGeBr3 halide perovskite compounds at different hydrostatic pressures, from 0 to 8 GPa. InGeCl3 and InGeBr3 halide perovskite exhibit noteworthy changes in their electronic and optical properties under different pressure conditions. When the pressure is 0 GPa, the direct bandgap for InGeCl3 is 0.886 eV, and for InGeBr3 it is 0.536 eV. This gap decreases as the pressure rises. Specifically, InGeBr3 exhibits conducting properties at 3 GPa due to its larger bromine atoms, whereas InGeCl3 requires a higher pressure of 6 GPa to achieve similar conductivity. This type of nature suggests that larger halogen atoms reduce the bandgap more effectively under pressure. As the pressure increases, the behavior of the lattice constant and unit cell volume decreases constantly, from 5.257 and 145.267 Å3 for InGeCl3 to 5.509 and 167.168 Å3 for InGeBr3 at 0 GPa for both compounds. When subjected to pressure, the bonds between In-X and Ge-X atoms experience compression, leading to a decrease in surface area and an enhancement in mechanical strength. Overall, the compounds exhibit characteristics of semiconductors, as evidenced by evaluations of their electrical properties. As pressure increases, the bandgap decreases linearly, narrowing until it aligns with the Fermi level, leading to a transition toward a metallic state. In addition, the pressure induces a rise in the electrical density of states around the Fermi level by displacing valence band electrons in an upward direction. As pressure increases, the electron density peak shifts to lower photon energy values. Notably, InGeCl3 exhibits a more pronounced shift in this peak compared to InGeBr3, indicating greater sensitivity to pressure. In terms of optical properties, both compounds demonstrate significant absorption coefficients in the visible region, suggesting their potential suitability for photovoltaic applications. The dielectric constant, absorption, and reflectivity values all increase gradually as pressure increases. The absorption spectra shift toward longer wavelengths. Furthermore, the mechanical properties analysis reveals that all InGeX3 compounds are mechanically stable up to 8 GPa pressure.